2022
DOI: 10.3390/antibiotics11060828
|View full text |Cite
|
Sign up to set email alerts
|

Companion Animals as Potential Reservoirs of Antibiotic Resistant Diarrheagenic Escherichia coli in Shandong, China

Abstract: Antibiotic resistance genes of Escherichia coli (E. coli) from companion animals were still poorly understood. Here, we investigated the extended-spectrum β-lactamases (ESBLs) resistance genes of E. coli from companion animals in Shandong, China. A total of 79 isolates (80.6%) were recovered from 98 healthy or diarrheal companion animals in 2021, among which ESBLs-producing isolates accounted for 43.0% (34/79), and more than half of ESBL E. coli (ESBL-EC) strains (n = 19) were isolated from healthy companion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 69 publications
4
11
1
Order By: Relevance
“…The results of this study are consistent with the high frequency of resistance to AMP and SXT reported for feline E. coli isolates in other studies [27,28]; however, the resistant rate to AMC (6.4%) was lower than that (15-100%) found in these studies. Moreover, all E. coli isolates were susceptible to MEM, suggesting the absence of carbapenems resistance among our isolates which is consistent with previous studies in cats from Australia [27] and China [19].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study are consistent with the high frequency of resistance to AMP and SXT reported for feline E. coli isolates in other studies [27,28]; however, the resistant rate to AMC (6.4%) was lower than that (15-100%) found in these studies. Moreover, all E. coli isolates were susceptible to MEM, suggesting the absence of carbapenems resistance among our isolates which is consistent with previous studies in cats from Australia [27] and China [19].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, E. coli was recovered from 28.2% and 55.5% of apparently healthy and diseased cats, respectively. A similar isolation rate (52%) was observed in diseased cats in Italy [26], whereas a higher isolate rate (45.6%) was found among apparently healthy cats in China [19].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…E. coli is an extremely divergent bacterial species with more than 200 O-serotypes differing by the structure of the O-polysaccharide repetitive unit described [ 9 , 52 , 53 ]. Many of these serotypes may feature pathogenic potential and cause different infections in humans and in animals [ 54 , 55 , 56 , 57 , 58 ]. For example, more than 50% of the urological infections in patients without anatomical anomalies are caused by uropathogenic E. coli , represented by more than 15 serotypes [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are the following six well-described categories: enteroaggregative E. coli (EAEC), enterohemorrhagic E. coli (EHEC), enteroinvasive E. coli (EIEC), enteropathogenic E. coli (EPEC), enterotoxigenic E. coli (ETEC), extraintestinal E. coli (ExPEC), and Shiga toxin-producing E. coli (STEC) based on clinical characteristics and virulence factors [ 1 ]. The worldwide emergence of multidrug-resistant E. coli isolated from human, animal, and animal-derived products warrants global surveillance [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%